Analisis perlakuan akuntansi aset tetap pada Badan Pengelola Keuangan dan Barang Milik Daerah Kota Manado - Carolina, Carolina; Manossoh, Hendrik; Lambey, Robert (Indonesia Accounting Journal, 2019)
The main task of government agencies is to provide services to the community whose quality can be improved by the use of fixed assets to achieve the duties and functions of government agencies. The presence of Government Regulation (PP) of the Republic of Indonesia Number 71 Year 2010 concerning Accrual Based Government Accounting Standards is the momentum of changes in Government Accounting Standards from previously cash-based to accruals, to accrual-based and have major implications for the treatment of assets where depreciation is taken into account in the valuation of fixed assets. The purpose of this research is to find out the accounting treatment of Fixed Assets that are applied to the Regional Finance and Asset Management Agency (BPK-AD) of Manado City in accordance with Government Regulation No. 71 of 2010 statement No. 07. The research method used in this study is qualitative research. The results showed that the recognition of fixed assets, measurement or valuation of fixed assets, and depreciation of assets in the BPK-AD Manado City are in accordance with SAP No. 07, as well as the Manado City BPK-AD in the management of regional assets following a separate regulation made by the Manado city BPK-AD namely the Technical Bulletin (Bultek) as a reference to regulate and adjust regional asset management in accordance with SAP No. 07.